Peningkatan Hasil Belajar Melalui Model Kooperatif Tipe Talking Stick dalam Pembelajaran Tematik Terpadu Kelas IV SD - Putri, Anggraini Cikita; S, Farida (Universitas Negeri Padang, 2021)
This research is motivated by the reality in the field which shows the low involvement of students in integrated thematic learning. This study aims to describe the improvement in student learning outcomes in integrated thematic learning through the Cooperstive Talking Stick type model in grade IV Elementary School. This type research is Clasroom Action Research using qualitative and quantitative approaches. The research subjects were grade IV students with 29 students of SDN 01 Ulak Karang. From the results of the study concluded that a) RPP showedthe results of improvement trough observations made by observers with an average score obtained in the observation of RPP cycle I was 84,72%, in the second cycle to 88,88%. b) the average value of the aspects of the first cycle teacher was 87,49%, in the second cycle 93,75%. c) the average value of aspects of the student in the first cycle 81,24%, in the second cycle 93,75%. Student learning outcomes in the first cycle obtained an average value of 68,76% and increased in the second cycle with an average value of 78,72%.